Self‐Healing SeO2 Additives Enable Zinc Metal Reversibility in Aqueous ZnSO4 Electrolytes. (22nd January 2022) - Huang, Cong; Zhao, Xin; Hao, Yisu; Yang, Yujie; Qian, Yang; Chang, Ge; Zhang, Yan; Tang, Qunli; Hu, Aiping; Chen, Xiaohua
Abstract: The development of aqueous zinc metal batteries (AZMBs) is significantly impeded by the poor cycle stability of Zn anodes due to the uncontrolled dendrite growth and low Coulombic efficiency (CE). Herein, for the first time, SeO2 additives are introduced into ZnSO4 electrolyte to enhance the stability of the Zn anode. According to the experimental results, the protective ZnSe layer is initially in‐situ formed on the Zn surface prior to the Zn plating, which acts as a shield for inhibiting the parasitic reactions and dendrite formation. Moreover, this additive strategy yields the unique characteristic of self‐healing for recovering the cracks in the consequence of huge volume change, ensuring the durability of ZnSe layer. Consequently, Zn|Zn symmetric cell using SeO2 additive delivers an enhanced cumulative plated capacity of 2.1 Ah cm −2 under practical test conditions, which far exceeds the previously reported works. Meanwhile, the average CE of 99.6% for 250 cycles is also demonstrated in Zn|Cu half cells with the presence of the SeO2 additive. In addition, the positive effect of the SeO2 additive is further illustrated in the Zn‐MnO2 full cells with a limited Zn. Abstract : SeO2 additive is first introduced as solid electrolyte interphase (SEI)−forming agent for stabilizing Zn anodes. With the addition of SeO2, Zn symmetric cells display a high cumulative plated capacity of 2.1 Ah cm −2 and a high average Coulombic efficiency of 99.6% under harsh test conditions (2 mA cm −2, 2 mAh cm −2 ).